HUBUNGAN ANTARA PEMBERIAN SUSU IBU HAMIL DAN TABLET Fe DENGAN PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DIWILAYAH KERJA PUSKESMASGAPURA SUMENEP - Sri Sumarni (Wiraraja Medika : Jurnal Kesehatan, 2012)
This research Anemia during pregnancy is a major public health problem in developingcountries. Deficiency anemia prevalence ranged between (12-43%). Maternal anemiaprevention programs in UPT Health Center Gapura Sumenep has done efforts included theprevention of early detection and treatment of anemia through antenatal care services. Givingmilk for pregnant woman and Fe tablets can raise levels of hemoglobin and can reduce theprevalence of anemia in pregnant women.This study is Comparing the increase in hemoglobin levels of anemic pregnant womenwho get the milk for pregnant woman and was given Fe tablets in the region of GapuraSumenep Health Center.This type of research is a quasi experimental, pretest and posttest control group design.Retrieval unit sample analysis performed by simple random sampling of the samples in thisstudy is 16 people. Analysis of the data used in this study is used paired t - test andIndependent samples t- test.There is a relationship between giving milk for pregnant woman with elevated levels of Hband there is a difference hb level between feeding groups of pregnant women milk andprovision of Fe tablet with p = 0.000 (p <0.05)There is a relationship between giving pregnant milk for pregnant woman milk with elevatedlevels of hemoglobin of pregnant women, and there are significant differences.Keywords: Giving milk for pregnant woman, Fe tablets, increased levels of Hb